Pengembangan Aplikasi Web Otomatisasi Survei Kondisi Jalan Menggunakan Sensor Ponsel Pintar (Studi Kasus PT. Hirfi Studio) - Yoga Saputra Hariyanto Kusumo; Achmad Arwan; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Roads are infrastructure that have an important role to support land transportation and support equitable development in an area., therefore road conditions must always be in good condition. In conducting monitoring, a survey is needed to determine the feasibility of road conditions. One survey method used is the International Roughness Index (IRI). PT. Hirfi Studio is a technical consultant company in Malang that provides transportation infrastructure survey services. PT. Hirfi Studio conducts surveys using direct visual observation method and then recorded manually on a survey form to be processed and converted into an IRI scale. The main tool used in conducting surveys are GPS, cameras and worksheets. The weakness of that processes are survey data in the paper form vulnerable to loss and damage, and processing data from the digitization of data to making maps takes a long time. Therefore, it is necessary to develop an automation survey on road condition using smart phone sensors to assist in conducting surveys. System development is done using software development life cycle (SDLC) waterfall model with object-oriented approach. The implementation of the application applies the model-view-controller (MVC) pattern in Codeigniter framework using HTML, PHP, CSS and Javascript programming language and uses database management system (DBMS) MySQL. In the testing phase, the unit testing value is 100% from 12 test cases, 100% validation of 46 test cases, and compatibility testing shows that the application can run on all desktop and smartphone web browsers.